Preparation method and application of diamond surface Al film

CN122918512APending Publication Date: 2026-10-16GUANGDONG UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611037873.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-13
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

对于金刚石表面Al膜的制备而言,由于Al与金刚石之间存在较大的物理性质差异,其界面润湿性和结合能力相对较弱

Benefits of technology

(1)本发明利用HiPIMS高离化率沉积方式,在金刚石表面构建“超薄Ti层-超薄Cr层-厚Al覆膜”的梯度界面结构。HiPIMS能够使溅射金属原子(如Ti、Cr、Al)的离化率水平达到90%以上,这些高能金属离子在基体偏压的作用下,对金刚石表面产生强烈的“自轰击”和“离子钉扎”效应。这不仅能彻底清除基体表面微观残留并活化碳键(形成致密的化学碳化物键合),还能显著打碎粗大的柱状晶,促进薄膜呈“原子级”的致密、光滑、铺展式生长,大幅消除薄膜内部的空洞缺陷,从而同时实现极高的附着力与极低的界面热阻。同时,Ti层增强金刚石基体与金属膜层的初期结合;Cr层优化界面过渡并改善Al膜生长条件;Al覆膜在连续致密过渡层基础上形成平整光滑的功能膜。这种梯度结构通过厚度与界面匹配设计,实现界面结合力与膜层生长质量的同步优化。即本发明通过HiPIMS高离化率沉积与Ti/Cr/Al梯度结构的协同作用,可获得高附着力、低界面热阻且表面光滑的Al膜。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122918512A_ABST
    Figure CN122918512A_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of surface modification, and particularly relates to a preparation method and application of a diamond surface Al film. The preparation method of the diamond surface Al film comprises the following steps: a Ti layer, a Cr layer and an Al film are sequentially deposited on the surface of a diamond substrate by using high-power pulse magnetron sputtering. The application utilizes a HiPIMS high-ionization-rate deposition mode to construct a gradient interface structure of "ultra-thin Ti layer-ultra-thin Cr layer-thick Al coating" on the surface of the diamond. The Ti layer enhances the initial combination of the diamond substrate and the metal film layer; the Cr layer optimizes the interface transition and improves the growth conditions of the Al film; and the Al coating forms a smooth functional film on the basis of the continuous and dense transition layer. The synergistic effect of the HiPIMS high-ionization-rate deposition and the Ti / Cr / Al gradient structure can obtain the Al film with high adhesion, low interface thermal resistance and smooth surface.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of surface modification technology, and specifically relates to a method for preparing an Al film on a diamond surface and its application. Background Technology

[0002] With the rapid development of high-tech fields such as 5G / 6G communication, third / fourth generation semiconductors (such as GaN, SiC, Ga2O3, etc.), and high-power radar, the integration and power density of electronic components have increased dramatically. The "heat dissipation" problem of chips has become an absolute bottleneck restricting the improvement of the performance and reliability of high-frequency, high-power electronic devices. Developing heat dissipation substrate materials with extremely high thermal conductivity has become the core direction of the development of modern thermal management systems.

[0003] Diamond possesses the highest thermal conductivity found in nature at room temperature (single-crystal diamond can reach over 2000 W / (m·K)), along with a low coefficient of thermal expansion, high insulation properties, and excellent mechanical stability, making it widely recognized as the ideal heat dissipation and packaging substrate material for next-generation high-power electronic devices. However, due to the extremely high chemical inertness of the diamond surface and its poor wettability with most metals (especially Al and Cu, which have excellent electrical and thermal conductivity), the adhesion of metal films deposited directly on the diamond surface is extremely low, resulting in very high thermal resistance. Under thermal cycling or high-current impact, the metal film layer is highly susceptible to peeling, flaking, or cracking.

[0004] Currently, methods for preparing metal films on diamond surfaces mainly include electroless plating, electroplating, magnetron sputtering, and evaporation deposition. For the preparation of Al films on diamond surfaces, due to the significant differences in physical properties between Al and diamond, their interfacial wettability and adhesion are relatively weak. When the Al film thickness increases to the micrometer level, the internal stress accumulation of the film becomes more pronounced, easily leading to problems such as localized delamination, cracks, and increased surface roughness, making it difficult to simultaneously achieve high adhesion, density, and surface smoothness.

[0005] Therefore, it is of great significance to develop a method for preparing Al films that can form highly bonded, dense and smooth Al films on diamond surfaces. Summary of the Invention

[0006] The present invention aims to solve one or more technical problems existing in the prior art, and at least provide a beneficial solution. Specifically, the present invention provides a method for preparing an Al film on a diamond surface, which can form an Al film with high adhesion, density, smoothness, and low thermal resistance on the diamond surface.

[0007] The inventive concept of this invention: The method for preparing an Al film on a diamond surface according to this invention includes the following steps: depositing a Ti layer, a Cr layer and an Al film sequentially on the surface of a diamond substrate using high-power pulsed magnetron sputtering.

[0008] This invention utilizes high-power pulsed magnetron sputtering (HiPIMS) with high ionization rate deposition to construct a gradient interface structure of "Ti layer-Cr layer-Al coating" on the diamond surface. HiPIMS can achieve an ionization rate of over 90% for sputtered metal atoms (such as Ti, Cr, and Al). Under the influence of substrate bias, these high-energy metal ions generate a strong "self-bombardment" and "ion pinning" effect on the diamond surface. This not only thoroughly removes microscopic residues on the substrate surface and activates carbon bonds (forming dense chemical carbide bonds), but also significantly breaks down coarse columnar crystals, promoting the growth of a dense, smooth, and spreadable film at the "atomic level," greatly eliminating voids and defects within the film, thereby simultaneously achieving extremely high adhesion and extremely low interfacial thermal resistance.

[0009] Simultaneously, the Ti layer enhances the initial bonding between the diamond substrate and the metal film; the Cr layer optimizes the interface transition and improves the growth conditions of the Al film; and the Al film forms a smooth and flat functional film on the basis of a continuous and dense transition layer. This gradient structure achieves simultaneous optimization of interfacial bonding and film growth quality through thickness and interface matching design.

[0010] This invention utilizes the synergistic effect of HiPIMS high ionization rate deposition and Ti / Cr / Al gradient structure to obtain an Al film with high adhesion, low interfacial thermal resistance and smooth surface without the need for subsequent processing such as electroplating or heat treatment.

[0011] Therefore, a first aspect of the present invention provides a method for preparing an Al film on a diamond surface.

[0012] Specifically, the method for preparing the Al film on the diamond surface includes the following steps: Ti, Cr and Al layers were sequentially deposited on the surface of a diamond substrate using high-power pulsed magnetron sputtering.

[0013] Preferably, the diamond matrix includes any one of chemical vapor deposition (CVD) single crystal diamond, CVD polycrystalline diamond self-supporting sheet, diamond microparticles, diamond / copper composite material, and diamond / aluminum composite material.

[0014] Preferably, the diamond substrate is subjected to ultrasonic cleaning, etching, and bias voltage glow discharge cleaning.

[0015] Preferably, the ultrasonic cleaning time is 10-30 minutes.

[0016] Preferably, ultrasonic cleaning is performed sequentially in acetone and isopropanol.

[0017] Preferably, the ultrasonic cleaning time in acetone is 5-15 minutes.

[0018] Preferably, the ultrasonic cleaning time in isopropanol is 5-15 minutes.

[0019] Preferably, after ultrasonic cleaning, the surface of the diamond substrate is dried with high-purity nitrogen gas, and then the diamond substrate is fixed on the substrate holder in the vacuum chamber for etching and bias voltage glow cleaning.

[0020] Preferably, the etching time is 1-10 minutes.

[0021] Preferably, the etching is performed using an Ar ion source.

[0022] Preferably, the bias voltage glow cleaning time is 1-60 min.

[0023] Preferably, the bias voltage glow cleaning voltage is 0~-1000V.

[0024] Preferably, the thickness of the Ti layer is 5-20 nm.

[0025] Preferably, the thickness of the Cr layer is 50-200 nm.

[0026] Preferably, the thickness of the Al film is 1-5 μm.

[0027] Specifically, this invention utilizes the HiPIMS high ionization rate deposition method to construct a gradient interface structure of "ultra-thin Ti layer-ultra-thin Cr layer-thick Al coating" on the diamond surface.

[0028] Preferably, before deposition, the deposition rates of Ti, Cr, and Al targets required for depositing each functional layer are independently measured and calibrated on the accompanying monocrystalline silicon substrate placed in the furnace under fixed discharge parameters.

[0029] Preferably, the deposition rate of the Ti layer is 1-50 nm / min.

[0030] Preferably, the deposition time of the Ti layer is 9.6-38.5 s.

[0031] Preferably, the deposition rate of the Cr layer is 1-50 nm / min.

[0032] Preferably, the deposition time of the Cr layer is 81-324 s.

[0033] Preferably, the deposition rate of the Al film is 1-50 nm / min.

[0034] Preferably, the deposition time of the Al film is 27-135 min.

[0035] Preferably, after the vacuum chamber is evacuated to the background vacuum level, an inert gas is introduced, and then deposition is carried out.

[0036] Preferably, the inert gas includes argon (Ar); more preferably, the argon includes high-purity argon.

[0037] Preferably, when depositing Ti and Cr layers, the power supply for the high-power pulsed magnetron sputtering is 100-300W.

[0038] Preferably, when depositing the Ti layer and Cr layer, both the Ti target and the Cr target are 3-inch metal targets.

[0039] Preferably, during the deposition of the Ti and Cr layers, the peak current density of the pulsed discharge target surface is 0.1-0.5 A / cm². 2 .

[0040] Preferably, when depositing the Al film, the power supply of the high-power pulsed magnetron sputtering is controlled to be 100-500W.

[0041] Preferably, when depositing the Al film, the Al target is an 8-inch metal target.

[0042] Preferably, during Al film deposition, the peak current density of the pulsed discharge target surface is 0.05-0.15 A / cm². 2 .

[0043] Preferably, during Al film deposition, the rotation drive speed of the diamond substrate support is 1-5 rpm to ensure uniform film thickness and surface smoothness over a large area of ​​the outermost Al coating surface.

[0044] Preferably, during the deposition, the working gas pressure inside the chamber is 0.1-0.5 Pa.

[0045] Specifically, the chamber is filled with a pure Ar atmosphere.

[0046] Preferably, the working temperature of the diamond matrix is ​​80-160℃.

[0047] Preferably, the bias voltage applied to the diamond matrix is ​​-50 to -200V.

[0048] Preferably, during the deposition, the pulse width (P) w The range is 10-300 μs.

[0049] Preferably, the frequency (f) during deposition is 50-2000Hz.

[0050] Preferably, during the deposition, the working distance (d) of the diamond matrix is ​​50-150 mm.

[0051] The second aspect of the present invention provides an application of diamond with a Ti layer, a Cr layer and an aluminum film deposited by the preparation method described in the first aspect of the present invention in high-power semiconductor thermal management, electronic device packaging and high-power heat dissipation components.

[0052] Compared with the prior art, the beneficial effects of the technical solution provided by the present invention are as follows: (1) This invention utilizes the HiPIMS high ionization deposition method to construct a gradient interface structure of "ultra-thin Ti layer - ultra-thin Cr layer - thick Al coating" on the diamond surface. HiPIMS can achieve an ionization rate of over 90% for sputtered metal atoms (such as Ti, Cr, and Al). Under the influence of the substrate bias voltage, these high-energy metal ions produce a strong "self-bombardment" and "ion pinning" effect on the diamond surface. This not only thoroughly removes microscopic residues on the substrate surface and activates carbon bonds (forming dense chemical carbide bonds), but also significantly breaks down coarse columnar crystals, promoting the "atomic-level" dense, smooth, and spreadable growth of the film, greatly eliminating void defects inside the film, thereby achieving both extremely high adhesion and extremely low interfacial thermal resistance. At the same time, the Ti layer enhances the initial bonding between the diamond substrate and the metal film layer; the Cr layer optimizes the interface transition and improves the Al film growth conditions; and the Al coating forms a smooth and flat functional film on the basis of a continuous dense transition layer. This gradient structure, through thickness and interface matching design, achieves simultaneous optimization of interfacial adhesion and film growth quality. Specifically, this invention, through the synergistic effect of HiPIMS high ionization deposition and the Ti / Cr / Al gradient structure, can obtain Al films with high adhesion, low interfacial thermal resistance, and smooth surfaces.

[0053] (2) The present invention can effectively reduce the number of defects inside the film layer, suppress columnar crystal formation, obtain a continuous and dense thin film structure, and significantly improve the interfacial bonding force and surface flatness, providing a reliable technical solution for high-power electronic device thermal management, high thermal conductivity packaging and high heat flux density applications. Attached Figure Description

[0054] Figure 1 This is a schematic diagram of the structure of the Ti layer / Cr layer / Al film on the surface of the diamond substrate of the present invention; Figure 2 This is a scanning electron microscope image of the Al film deposited on the surface of a diamond substrate in Comparative Example 4 of the present invention. Figure 3 This is a scanning electron microscope image of the Al film deposited on the surface of a diamond substrate in Example 15 of the present invention; Figure 4 The transient thermal reflection test results of Embodiment 15 of the present invention and commercially available diamond metallized products are shown. Detailed Implementation

[0055] To enable those skilled in the art to more clearly understand the technical solutions described in this invention, the following embodiments are provided for illustration. It should be noted that the following embodiments do not constitute a limitation on the scope of protection claimed by this invention.

[0056] Unless otherwise specified, the raw materials, reagents or devices used in the following examples are available from conventional commercial sources or can be obtained by existing known methods.

[0057] In the following embodiments, the structural schematic diagram of the Ti layer / Cr layer / Al film on the diamond substrate surface is shown below. Figure 1 As shown.

[0058] Example 1 This embodiment provides a method for preparing an Al film on a diamond surface, the specific steps of which are as follows: (1) Substrate treatment The CVD single-crystal diamond substrate was first placed in acetone solvent and then in isopropanol solvent for ultrasonic cleaning for 15 min each. After cleaning, the substrate surface was dried with high-purity nitrogen. The diamond substrate was then fixed on the substrate tray in the vacuum chamber and evenly arranged along the circumference of a concentric circle with a radius of 2.5 cm centered on the center of the tray to ensure that each substrate has consistent deposition conditions and improve the uniformity of film thickness and performance. The distance between the target and the substrate was 82 mm. Ar ion source etching was performed for 1 min first, and then bias voltage glow cleaning was performed for 60 min in an argon atmosphere of 2 Pa. The bias voltage glow cleaning voltage was -800 V. (2) Multi-target deposition rate calibration On the monocrystalline silicon substrate placed in the furnace for subsequent high ionization discharge deposition of each functional layer, the monolayer deposition rates of Ti, Cr and Al targets required for deposition were independently measured and calibrated under fixed discharge parameters. (3) Deposition of Ti / Cr / Al thin films Evacuate the vacuum chamber to the background vacuum level (1×10⁻⁶). -4 After Pa), high-purity Ar gas is introduced to carry out the deposition of each layer: Ti layer deposition: A 3-inch Ti target was used, and the HiPIMS power supply was 250W with a pulse width (P0). w The time interval (f) is 100 μs, the frequency (f) is 400 Hz, and the peak current density is 0.4 A / cm². 2 The standard deposition rate under these discharge parameters was 31.1 nm / min, the bias voltage was -60 V, the chamber was heated to 120 °C, the chamber was facing the deposition, the discharge was run for 9.7 s and then shut off, resulting in a 5 nm Ti layer.

[0059] Cr layer deposition: A 3-inch Cr target was used, and the HiPIMS power supply operated at 250W. wThe time interval is 80 μs, the frequency f is 350 Hz, and the peak current density is adjusted to 0.4 A / cm². 2 The standard deposition rate under these discharge parameters is 37.0 nm / min, the bias voltage is -60 V, the chamber is heated to 120 °C, the chamber is directly facing the deposition, the discharge runs for 81.1 s and then shuts off, resulting in a 50 nm Cr layer.

[0060] Al film deposition: An 8-inch Al target was used, and the HiPIMS power supply operated at 300W. w The time interval is 110 μs, the frequency f is 300 Hz, and the peak current density is adjusted to 0.15 A / cm. 2 The standard deposition rate under these discharge parameters was 37.0 nm / min, the bias voltage was -60 V, the substrate rotation speed was 5 rpm, and the continuous discharge was run for 27 min before being shut off. After the Al film deposition was completed, the sample was cooled to below 50 °C and removed, resulting in a 1 μm Al film.

[0061] Example 2 The structural design of the Ti / Cr / Al multilayer thin film in Example 2 is as follows, and the rest is the same as in Example 1: Target thickness design: the bottom Ti layer is 5nm, the middle Cr layer is 100nm, and the outermost Al film is 1μm.

[0062] Discharge time for each layer: Ti target discharge was started and run for 9.7s and then stopped; Cr target discharge was started and run for 162.2s and then stopped; finally Al target discharge was started (matrix rotation 5rpm) and run continuously for 27min and then stopped.

[0063] Example 3 The structural design of the Ti / Cr / Al multilayer film in Example 3 is as follows, and the rest is the same as in Example 1: Target thickness design: bottom Ti layer is 5nm, middle Cr layer is 150nm, and outermost Al film is 1μm.

[0064] Discharge time for each layer: Ti target discharge was started and run for 9.7s and then stopped; Cr target discharge was started and run for 243.2s and then stopped; finally Al target discharge was started (matrix rotation 5rpm) and run continuously for 27min and then stopped.

[0065] Example 4 The structural design of the Ti / Cr / Al multilayer film in Example 4 is as follows, and the rest is the same as in Example 1: Target thickness design: the bottom Ti layer is 5nm, the middle Cr layer is 200nm, and the outermost Al film is 1μm.

[0066] Discharge time for each layer: Ti target discharge was started and run for 9.7s and then stopped; Cr target discharge was started and run for 324.3s and then stopped; finally Al target discharge was started (matrix rotation 5rpm) and run continuously for 27min and then stopped.

[0067] Example 5 The structural design of the Ti / Cr / Al multilayer thin film in Example 5 is as follows, and the rest is the same as in Example 1: Target thickness design: bottom Ti layer is 8nm, middle Cr layer is 100nm, and outermost Al film is 1.5μm.

[0068] Discharge time for each layer: Ti target discharge was started and run for 15.4s and then stopped; Cr target discharge was started and run for 162.2s and then stopped; finally Al target discharge was started (matrix rotation 5rpm) and run continuously for 40.5min and then stopped.

[0069] Example 6 The structural design of the Ti / Cr / Al multilayer film in Example 6 is as follows, and the rest is the same as in Example 1: Target thickness design: the bottom Ti layer is 10nm, the middle Cr layer is 50nm, and the outermost Al film is 2μm.

[0070] Discharge time for each layer: Ti target discharge was started and run for 19.3s and then stopped; Cr target discharge was started and run for 81.1s and then stopped; finally Al target discharge was started (matrix rotation 5rpm) and run continuously for 54min and then stopped.

[0071] Example 7 The structural design of the Ti / Cr / Al multilayer thin film in Example 7 is as follows, and the rest is the same as in Example 1: Target thickness design: the bottom Ti layer is 10nm, the middle Cr layer is 100nm, and the outermost Al film is 2μm.

[0072] Discharge time for each layer: Ti target discharge was started and run for 19.3s and then stopped; Cr target discharge was started and run for 162.2s and then stopped; finally Al target discharge was started (matrix rotation 5rpm) and run continuously for 54min and then stopped.

[0073] Example 8 The structural design of the Ti / Cr / Al multilayer film in Example 8 is as follows, and the rest is the same as in Example 1: Target thickness design: bottom Ti layer is 10nm, middle Cr layer is 150nm, and outermost Al film is 2μm.

[0074] Discharge time for each layer: Ti target discharge was started and run for 19.3s and then stopped; Cr target discharge was started and run for 243.2s and then stopped; finally Al target discharge was started (matrix rotation 5 rpm) and run continuously for 54 minutes and then stopped.

[0075] Example 9 The structural design of the Ti / Cr / Al multilayer film in Example 9 is as follows, and the rest is the same as in Example 1: Target thickness design: the bottom Ti layer is 10nm, the middle Cr layer is 200nm, and the outermost Al film is 2μm.

[0076] Discharge time for each layer: Ti target discharge was started and run for 19.3s and then stopped; Cr target discharge was started and run for 324.3s and then stopped; finally Al target discharge was started (matrix rotation 5rpm) and run continuously for 54min and then stopped.

[0077] Example 10 The structural design of the Ti / Cr / Al multilayer film in Example 10 is as follows, and the rest is the same as in Example 1: Target thickness design: bottom Ti layer is 12nm, middle Cr layer is 120nm, and outermost Al film is 2.5μm.

[0078] Discharge time for each layer: Ti target discharge was started and run for 23.2s and then stopped; Cr target discharge was started and run for 194.6s and then stopped; finally Al target discharge was started (matrix rotation 5rpm) and run continuously for 67.5min and then stopped.

[0079] Example 11 The structural design of the Ti / Cr / Al multilayer film in Example 11 is as follows, and the rest is the same as in Example 1: Target thickness design: the bottom Ti layer is 15nm, the middle Cr layer is 50nm, and the outermost Al film is 3μm.

[0080] Discharge time for each layer: Ti target discharge was started and run for 28.9s and then stopped; Cr target discharge was started and run for 81.1s and then stopped; finally Al target discharge was started (matrix rotates 5rpm) and run continuously for 81min and then stopped.

[0081] Example 12 The structural design of the Ti / Cr / Al multilayer film in Example 12 is as follows, and the rest is the same as in Example 1: Target thickness design: bottom Ti layer is 15nm, middle Cr layer is 100nm, and outermost Al film is 3μm.

[0082] Discharge time for each layer: Ti target discharge was started and run for 28.9s and then stopped; Cr target discharge was started and run for 162.2s and then stopped; finally Al target discharge was started (matrix rotation 5rpm) and run continuously for 81min and then stopped.

[0083] Example 13 The structural design of the Ti / Cr / Al multilayer film in Example 13 is as follows, and the rest is the same as in Example 1: Target thickness design: bottom Ti layer is 15nm, middle Cr layer is 150nm, and outermost Al film is 3μm.

[0084] Discharge time for each layer: Ti target discharge was started and run for 28.9s and then stopped; Cr target discharge was started and run for 243.2s and then stopped; finally Al target discharge was started (matrix rotation 5rpm) and run continuously for 81min and then stopped.

[0085] Example 14 The structural design of the Ti / Cr / Al multilayer film in Example 14 is as follows, and the rest is the same as in Example 1: Target thickness design: the bottom Ti layer is 15nm, the middle Cr layer is 200nm, and the outermost Al film is 3μm.

[0086] Discharge time for each layer: Ti target discharge was started and run for 28.9s and then stopped; Cr target discharge was started and run for 324.3s and then stopped; finally Al target discharge was started (matrix rotation 5rpm) and run continuously for 81min and then stopped.

[0087] Example 15 The structural design of the Ti / Cr / Al multilayer film in Example 15 is as follows, and the rest is the same as in Example 1: Target thickness design: bottom Ti layer is 18nm, middle Cr layer is 100nm, and outermost Al film is 3.5μm.

[0088] Discharge time for each layer: Ti target discharge was started and run for 34.7s and then stopped; Cr target discharge was started and run for 162.2s and then stopped; Al target discharge was started (matrix rotation 5rpm) and run continuously for 94.5min and then stopped.

[0089] Example 16 The structural design of the Ti / Cr / Al multilayer film in Example 16 is as follows, and the rest is the same as in Example 1: Target thickness design: bottom Ti layer is 20nm, middle Cr layer is 50nm, and outermost Al film is 4μm.

[0090] Discharge time for each layer: Ti target discharge was started and run for 38.6s and then stopped; Cr target discharge was started and run for 81.1s and then stopped; finally Al target discharge was started (matrix rotation 5rpm) and run continuously for 108min and then stopped.

[0091] Example 17 The structural design of the Ti / Cr / Al multilayer film in Example 17 is as follows, and the rest is the same as in Example 1: Target thickness design: the bottom Ti layer is 20nm, the middle Cr layer is 100nm, and the outermost Al film is 4μm.

[0092] Discharge time for each layer: Ti target discharge was started and run for 38.6s and then stopped; Cr target discharge was started and run for 162.2s and then stopped; finally Al target discharge was started (matrix rotation 5rpm) and run continuously for 108min and then stopped.

[0093] Example 18 The structural design of the Ti / Cr / Al multilayer film in Example 18 is as follows, and the rest is the same as in Example 1: Target thickness design: bottom Ti layer is 20nm, middle Cr layer is 150nm, and outermost Al film is 4μm.

[0094] Discharge time for each layer: Ti target discharge was started and run for 38.6s and then stopped; Cr target discharge was started and run for 243.2s and then stopped; finally Al target discharge was started (matrix rotation 5rpm) and run continuously for 108min and then stopped.

[0095] Example 19 The structural design of the Ti / Cr / Al multilayer film in Example 19 is as follows, and the rest is the same as in Example 1: Target thickness design: bottom Ti layer is 20nm, middle Cr layer is 200nm, and outermost Al film is 4μm.

[0096] Discharge time for each layer: Ti target discharge was started and run for 38.6s and then stopped; Cr target discharge was started and run for 324.3s and then stopped; finally Al target discharge was started (matrix rotation 5rpm) and run continuously for 108min and then stopped.

[0097] Example 20 The structural design of the Ti / Cr / Al multilayer film in Example 20 is as follows, and the rest is the same as in Example 1: Target thickness design: bottom Ti layer is 10nm, middle Cr layer is 130nm, and outermost Al film is 4.5μm.

[0098] Discharge time for each layer: Ti target discharge was started and run for 19.3s and then stopped; Cr target discharge was started and run for 210.8s and then stopped; finally Al target discharge was started (matrix rotation 5rpm) and run continuously for 121.5min and then stopped.

[0099] Example 21 The structural design of the Ti / Cr / Al multilayer film in Example 21 is as follows, and the rest is the same as in Example 1: Target thickness design: the bottom Ti layer is 5nm, the middle Cr layer is 100nm, and the outermost Al film is 5μm.

[0100] Discharge time for each layer: Ti target discharge was started and run for 9.7s and then stopped; Cr target discharge was started and run for 162.2s and then stopped; finally Al target discharge was started (matrix rotation 5rpm) and run continuously for 135min and then stopped.

[0101] Example 22 The structural design of the Ti / Cr / Al multilayer film in Example 22 is as follows, and the rest is the same as in Example 1: Target thickness design: the bottom Ti layer is 10nm, the middle Cr layer is 100nm, and the outermost Al film is 5μm.

[0102] Discharge time for each layer: Ti target discharge was started and run for 19.3s and then stopped; Cr target discharge was started and run for 162.2s and then stopped; finally Al target discharge was started (matrix rotation 5rpm) and run continuously for 135min and then stopped.

[0103] Example 23 The structural design of the Ti / Cr / Al multilayer film in Example 23 is as follows, and the rest is the same as in Example 1: Target thickness design: bottom Ti layer is 15nm, middle Cr layer is 100nm, and outermost Al film is 5μm.

[0104] Discharge time for each layer: Ti target discharge was started and run for 28.9s and then stopped; Cr target discharge was started and run for 162.2s and then stopped; finally Al target discharge was started (matrix rotation 5rpm) and run continuously for 135min and then stopped.

[0105] Example 24 The structural design of the Ti / Cr / Al multilayer film in Example 24 is as follows, and the rest is the same as in Example 1: Target thickness design: the bottom Ti layer is 20nm, the middle Cr layer is 100nm, and the outermost Al film is 5μm.

[0106] Discharge time for each layer: Ti target discharge was started and run for 38.6s and then stopped; Cr target discharge was started and run for 162.2s and then stopped; finally Al target discharge was started (matrix rotation 5rpm) and run continuously for 135min and then stopped.

[0107] Example 25 The structural design of the Ti / Cr / Al multilayer film in Example 25 is as follows, and the rest is the same as in Example 1: Target thickness design: the bottom Ti layer is 20nm, the middle Cr layer is 200nm, and the outermost Al film is 5μm.

[0108] Discharge time for each layer: Ti target discharge was started and run for 38.6s and then stopped; Cr target discharge was started and run for 324.3s and then stopped; finally Al target discharge was started (matrix rotation 5rpm) and run continuously for 135min and then stopped.

[0109] Comparative Example 1 The structural design of the thin film in Comparative Example 1 is as follows, and other aspects are the same as in Example 1: Target thickness design: The bottom Cr layer is 100nm and the outermost Al coating is 2μm.

[0110] Discharge time for each layer: After 162.2 seconds of discharge operation on the Cr target, the discharge was turned off; finally, the discharge operation on the Al target (with the matrix rotating at 5 rpm) was carried out continuously for 54 minutes before being turned off.

[0111] Comparative Example 2 The structural design of the thin film in Comparative Example 2 is as follows, and other aspects are the same as in Example 1: Target thickness design: The bottom Ti layer is 10nm and the outermost Al film is 2μm.

[0112] Discharge time for each layer: The Ti target was turned on and discharged for 19.3 seconds, then turned off; the Al target was then turned on (the matrix rotates at 5 rpm) and discharged continuously for 54 minutes, then turned off.

[0113] Comparative Example 3 The structural design of the thin film in Comparative Example 3 is as follows, and other aspects are the same as in Example 1: Target thickness design: 2 μm for Al coating only.

[0114] Discharge time for each layer: After continuous discharge for 54 minutes with the Al target turned on (substrate rotating at 5 rpm), the discharge was turned off.

[0115] Comparative Example 4 Comparative Example 4 uses conventional low-ionization DC magnetron sputtering (DCMS) to prepare Al films. The specific preparation steps are as follows: (1) Matrix cleaning and fixation: The diamond matrix self-supporting sheet was ultrasonically cleaned in acetone and isopropanol for 15 minutes respectively, dried and fixed on the matrix bracket in the vacuum chamber.

[0116] (2) Conventional DC continuous deposition: The chamber is evacuated to the background vacuum level (1×10⁻⁶). -4 After passing through a high-purity Ar gas, the working pressure was kept constant at 0.4 Pa, the substrate working temperature was 120℃, and a DC substrate bias voltage of -60V was applied. Under these conditions, instead of using a high-power pulsed magnetron sputtering power supply, a DC power supply was used to discharge and deposit the bottom Ti layer at a power of 250W for 12.9 s. Then, the process was switched to the intermediate Cr target, and a discharge and deposition of the intermediate Cr layer was performed at a DC power of 250W for 108.1 s. Finally, the process was switched to the outer Al target, and a discharge and deposition of the outer Al coating was performed at a DC power of 300W for 36.0 min.

[0117] Performance testing 1. Tape adhesion test The adhesion of the coating was tested using the 3M high-strength pressure-sensitive tape peel method. The 3M high-strength pressure-sensitive tape was applied to the surface of the Al film and then peeled off. The residual coverage rate of the Ti / Cr / Al metal film after peeling was recorded (film coverage rate). The adhesion was judged based on the size of the residual coverage rate of the metal film after peeling. The larger the residual coverage rate, the better the adhesion.

[0118] The adhesive tape adhesion test results of the diamond Al films prepared in Examples 1-25 and Comparative Examples 1-4 are shown in Table 1.

[0119] Table 1: Test results of tape adhesion on the surface of diamond Al films prepared in Examples 1-25 and Comparative Examples 1-4

[0120] As can be seen from Table 1, the Ti / Cr / AL multilayer film deposited on the diamond surface of the present invention exhibits excellent adhesion, meeting the operational requirements.

[0121] Comparative Example 1 had no Ti layer, Comparative Example 2 had no Cr layer, and Comparative Example 3 had neither Ti nor Cr layers. This resulted in significantly lower film coverage in Comparative Examples 1-3 compared to the examples. This demonstrates that Ti and Cr layers, acting as intermediate transition layers, can improve interfacial adhesion.

[0122] Comparative Example 4 employed low-ionization DC magnetron sputtering, resulting in a significantly lower film coverage compared to the Example. This demonstrates the crucial role HiPIMS plays in enhancing interfacial adhesion.

[0123] 2. Scanning electron microscopy observation Scanning electron microscopy (SEM) images of the deposited Al films on the diamond substrates of Comparative Example 4 and Example 15 are shown below. Figure 2 and 3 As shown.

[0124] Depend on Figure 2 As can be seen, the thin film in Comparative Example 4 exhibits a coarse-grained structure with gaps and low density. Figure 3 As can be seen, the film surface exhibits a fine structure with high flatness and density. This demonstrates that the present invention can obtain a smooth and dense Al film by depositing Al films using HiPIMS.

[0125] 3. Transient thermal reflection test Transient thermal reflection tests were performed on Example 15 and commercially available diamond metallized products. The transient thermal reflection test used a femtosecond laser as the pump light to instantaneously heat the sample surface, and the changes in the thermal reflection signal of the sample surface were monitored in real time using a delayed probe light. The thermal diffusion capability and interfacial thermal transport performance of the sample were evaluated based on the thermal reflection signal attenuation curve.

[0126] Transient thermal reflection test results are as follows Figure 4 As shown, the thermal reflection signal attenuation rate of Example 15 is significantly faster than that of commercially available diamond metallized products, indicating that heat can be transferred from the sample surface to the interior more quickly, exhibiting superior thermal diffusion capability and interfacial thermal transport performance. Compared to commercially available diamond metallized products, the Ti / Cr / Al gradient structure constructed in this invention reduces the interfacial thermal resistance between the metal film and the diamond substrate, improves the interfacial heat transfer efficiency, and thus effectively improves the heat dissipation performance of the diamond substrate.

[0127] In summary, this invention achieves a high-adhesion, low-interfacial thermal resistance, and smooth-surfaced Al film through the synergistic effect of HiPIMS high ionization rate deposition and Ti / Cr / Al gradient structure.

[0128] The above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the essence and scope of the technical solutions of the present invention.

Claims

1. A method for preparing an Al film on a diamond surface, characterized in that, Includes the following steps: Ti, Cr and Al layers were sequentially deposited on the surface of a diamond substrate using high-power pulsed magnetron sputtering.

2. The preparation method according to claim 1, characterized in that, The diamond matrix includes any one of the following: chemical vapor deposition single crystal diamond, chemical vapor deposition polycrystalline diamond self-supporting sheet, diamond microparticles, diamond / copper composite material, and diamond / aluminum composite material.

3. The preparation method according to claim 1, characterized in that, The diamond matrix is ​​subjected to ultrasonic cleaning, etching, and bias voltage glow cleaning.

4. The preparation method according to claim 3, characterized in that, The ultrasonic cleaning time is 10-30 minutes; And / or, the etching time is 1-10 min; And / or, the bias voltage glow cleaning time is 1-60 min; And / or, the bias voltage glow cleaning voltage is 0~-1000V.

5. The preparation method according to claim 1, characterized in that, The thickness of the Ti layer is 5-20 nm; And / or, the thickness of the Cr layer is 50-200 nm; And / or, the thickness of the Al film is 1-5 μm.

6. The preparation method according to claim 1, characterized in that, The deposition rate of the Ti layer is 1-50 nm / min; And / or, the deposition time of the Ti layer is 9.6-38.5 s; And / or, the deposition rate of the Cr layer is 1-50 nm / min; And / or, the deposition time of the Cr layer is 81-324 s; And / or, the deposition rate of the Al film is 1-50 nm / min; And / or, the deposition time of the Al film is 27-135 min.

7. The preparation method according to claim 1, characterized in that, After the vacuum chamber is evacuated to the background vacuum level, an inert gas is introduced, and then deposition is carried out; And / or, when depositing Ti or Cr layers, the power supply for the high-power pulsed magnetron sputtering is 100-300W. And / or, when depositing Ti or Cr layers, the peak current density of the pulsed discharge target surface is 0.1-0.5 A / cm². 2 .

8. The preparation method according to claim 1, characterized in that, When depositing Al films, the power supply of the high-power pulsed magnetron sputtering system is controlled to be 100-500W. And / or, during Al film deposition, the peak current density of the pulsed discharge target surface is controlled to be 0.05-0.15 A / cm². 2 ; And / or, during Al film deposition, the rotation drive speed of the diamond substrate support is 1-5 rpm.

9. The preparation method according to claim 1, characterized in that, During deposition, the working gas pressure inside the chamber is 0.1-0.5 Pa; And / or, the working temperature of the diamond matrix is ​​80-160℃; And / or, the bias voltage applied to the diamond matrix is ​​-50 to -200V.

10. The application of diamond with Ti, Cr and Al layers deposited on it, prepared by the method according to any one of claims 1-9, in high-power semiconductor thermal management, electronic device packaging, and high-power heat dissipation components.